Impact of oil and related chemicals on the marine environment (GESAMP, 1993)
The review describes the hazards of marine oil pollution and associated chemicals and wastes as they are understood currently, and clarifies the importance of reducing oil inputs in coastal and decision-makers alike, such as: how much oil is entering our oceans, and how much harm is it doing.